Stable serum resistance of Neisseria gonorrhoeae as an epidemiological marker. - Lavitola, A (1984)
Using a simple and rapid microassay, we tested 100 strains of Neisseria gonorrhoeae isolated from 81 patients (41 men and 40 women) for their sensitivity to killing by normal human serum (NHS). The reproducibility of the test was good when the bactericidal end points were taken as the dilution of fresh NHS that killed more than 95% of the test organisms. The bactericidal end points of strains isolated either from different anatomical sites or from sexual partners correlated well with the levels of sensitivity to serum of corresponding isolates, as well as with auxotypes. When the strains were not highly resistant to killing by NHS, this marker gave a precise definition of each strain and permitted the differentiation of isolates belonging to common auxotypes.